Tingkat Kecemasan Atlet Petanque Universitas Pendidikan Mandalika Saat Menghadapi Pertandingan - Muliyani, Sri Erny; Syah, Herman (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
Anxiety is a psychological factor that can affect an athlete's performance, especially in individual sports such as Petanque. This study aims to determine the anxiety level of Mandalika Education University (UNDIKMA) Petanque athletes when competing and identify management strategies. This research uses a quantitative approach with a survey method. The research instrument was a questionnaire adapted from the Sport Anxiety Scale-2 (SAS-2) and distributed to 22 UNDIKMA Petanque athletes. Data was analyzed quantitatively descriptively. The results showed that the majority of athletes had anxiety levels in the medium category, 9 people (40.91%), 6 people in the low category (27.27%), 4 people in the high category (18.18%), very high category. as many as 2 people (9.09%), and the very low category was only 1 person (4.55%). The dominant anxiety felt by athletes is somatic anxiety, such as increased heart rate and muscle tension, which has an impact on performance when competing. The conclusion of this research shows that the anxiety level of UNDIKMA Petanque athletes is in the medium category. Therefore, it is recommended that coaches and team management implement psychological training programs, such as Psychological Skills Training (PST) and emotional intelligence development, to help athletes manage anxiety. Apart from that, optimizing social support from coaches, family and teammates is also needed to create a competition environment that supports optimal performance.